Analisis Preferensi Bunga Krisan (Chrysanthemum morifolium r) di Pusat Promosi dan Pemasaran Bunga dan Tanaman Hias, Rawa Belong, Jakarta Barat - Purnamasari, Asih; Novita, Ita; Yusdiarti, Arti (Universitas Djuanda Bogor, 2017)
The purpose of this study is to identify and assess the consumer characteristics of chrysanthemum plants at Pusat Promosi dan Pemasaran Bunga dan Tanaman Hias Rawa Belong, West Jakarta, and analyze consumer preferences towards attributes chrysanthemum plants andanalyze the level of customer satisfaction of chrysanthemum plants. The analysis used is descriptive analysis, Importance Performance Analysis (IPA) using Minitab 16 and the analysisof Customer Satisfaction Index (CSI). The results showed the average level of performance of chrysanthemum plants was 4,07 and the average level of consumer interest is 4,19 with acompliance rate of 97,06%, so it can be said that the performance of chrysanthemum plants have to meet consumer expectations. CSI value amounted to 81,87% at an interval of 80-100% can be interpreted so that consumers are satisfied with the performance of the marketing mix PusP2BTH Rawa Belong West Jakarta.Keywords: Consumer Preferences, Chrysanthemum, IPA, CSI